Asuhan Keperawatan pada Ny. D Dengan Post Operasi Sectio Caesarea Indikasi Riwayat Sectio Caesarea di Ruang Nusa Indah Rsud Dr. Soeselo Kabupaten Tegal - Lintang Cahya Ningrum; Tati Karyawati; Siti Fatimah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Using chemical drugs to relieve pain after caesarean section surgery can cause dangerous side effects when used for a long time. The aim of this research is to provide nursing care for postpartum mothers and caesarean section mothers including: assessment, diagnosis, planning, implementation and evaluation. In writing this scientific work, the author used methods including: observation, interviews, documentation, and literature study. There are 5 analytical methods used, namely: assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. During the assessment, pain and sleep disturbances were found. The nursing diagnosis showed that there was a wound in the lower abdomen from the operation. Nursing intervention by providing health education materials and media so that knowledge increases. Implement health care by removing the dressing slowly, cleaning with NaCl fluid, and monitoring for signs of infection. Nursing evaluation found that cleaning the wound and changing the dressing had no complaints and the wound on the stomach was dry, there was no redness and there were no signs of infection. The application can provide good nursing care for caesarean-section mothers and increase knowledge about parenting patterns for mothers who have had caesarean-section operations.